Pelatihan Penelitian Tindakan Kelas bagi Guru MTs di Kota Palangkaraya - Sabarun; Akhmad Ali Mirza; Jhon Sarip; Tazkiyatunnafs Elhawwa (LPPM IAI Hasanuddin Pare-Kediri, 2024)
This service activity aimed to provide training to Madrasah Tsanawiyah teachers in compiling scientific papers in the form of Classroom Action Research. Apart from that, it trains teachers to carry out research activities in the classroom to develop their profession. The participants in this activity were 25 teachers at MTs Negeri 2 Palangka Raya. This activity was held in the Meeting Room of MTs Negeri 2 Palangka Raya on December 15 2023. Material was provided by Sabarun, M.Pd. which relates to guidelines for preparing scientific papers which consist of procedures in classroom action research and learning models that can be used in the teaching and learning process. This activity produces a draft proposal for Classroom Action Research using appropriate cycles. During the activity, participants were enthusiastic and produced PTK proposals with various titles. It could be showed that this service activity was running well and obtaining maximum results.